Pengembangan Media Pembelajaran Digital Pop-Up Book Berbasis Powerpoint Interaktif Materi Pendengaran Kelas V Sekolah Dasar - Muhammad Aziz Nur Huda; Siti Maryatul Kiptiyah (Postgraduate, University of Mataram, 2024)
The creation of pop-up book learning materials based on PowerPoint can improve learning results and student interest. The purpose of this study was to determine the feasibility pop-up book learning materials based on PowerPoint and its effect on students' listening comprehension on sound-based material. This research is a development research (R&D) using the ADDIE model development design, which consists of five stages namely analysis, design, development, implementation, and evaluation. The results showed that the effectiveness of PowerPoint-based pop-up book was 97% based on the average validation of media experts, 95% based on the validation of teaching material experts, 95% based on the results of the classroom teacher response questionnaire and 95% based on the results of the student response questionnaire. Pop-up books with a PowerPoint foundation fall under the category of educational resources that are useful for learning. The N-gain test results also show that the learning media developed by researchers are in the very feasible category. In other words, it can be concluded that PowerPoint-based pop-up book learning media is effective, practical and efficient in improving student learning outcomes in elementary schools.